Analisis Determinan Volume Ekspor Pala Indonesia dalam Jangka Panjang dan Jangka Pendek - Alawi, Muhammad Ridwan; Renaldi, Eddy (Universitas Galuh, 2025)
Nutmeg is an Indonesian spice commodity with the highest export value in the past five years. Although Indonesia still dominates the global nutmeg market, its export volume growth rate tends to lag behind competitor countries, especially re-exporting countries. This study aims to analyze the determinants of Indonesian nutmeg export volume to the ten main importing countries in both the long and short-run. The data used are secondary data from 1994–2023, analyzed using the Error Correction Mechanism (ECM) estimation method. ECM analysis indicates that, in both the long and short-run, domestic production has an insignificant effect, Indonesia's GDP has a significant negative effect, while the GDP of destination countries, export price index, and exchange rate have significant positive effects on Indonesian nutmeg export volume to the ten main importing countries. Additionally, the population of destination countries has a significant positive effect in the long-run but is insignificant in the short-run. Moreover, the variable in the short-run has a significant negative effect on Indonesian nutmeg export volume the ten main importing countries.